2014
DOI: 10.1111/jcc4.12057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Online Comments on Smokers' Perception of Antismoking Public Service Announcements

Abstract: On YouTube anti-smoking PSAs are widely viewed and uploaded; they also receive extensive commentary by viewers. This study examined whether such evaluative comments with or without uncivil expressions influence evaluations by subsequent viewers. Results showed PSAs with positive (i.e. anti-smoking) comments were perceived by smokers as more effective than PSAs with negative (pro smoking) comments. Smokers in the no comment condition gave the highest perceived effectiveness score to PSAs. Smokers’ readiness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 36 publications
6
56
1
1
Order By: Relevance
“…Though research examining the content and nature of online comments is still in its infancy (Regan et al, 2014), scholars agree that internet-based technologies create spaces in which the general public can discuss, deliberate upon, and question current events (Blom, Carpenter, Bowe, &Lange, 2014;Coe, Kenski, & Rains, 2014), including health-related stories (Holton et al, 2014). Moreover, analysis of online comments can reveal the core issues that readers notice, attend to, and react to as they consume celebrity health stories (Shi, Messaris, & Cappella, 2014), suggesting which stories, issues, and articles "readers really care about" (Laslo, Baram-Tsabari, & Lewestein, 2011, p. 865).…”
Section: Understanding Reactions To Celebrity Narratives Through Onlimentioning
confidence: 99%
“…Though research examining the content and nature of online comments is still in its infancy (Regan et al, 2014), scholars agree that internet-based technologies create spaces in which the general public can discuss, deliberate upon, and question current events (Blom, Carpenter, Bowe, &Lange, 2014;Coe, Kenski, & Rains, 2014), including health-related stories (Holton et al, 2014). Moreover, analysis of online comments can reveal the core issues that readers notice, attend to, and react to as they consume celebrity health stories (Shi, Messaris, & Cappella, 2014), suggesting which stories, issues, and articles "readers really care about" (Laslo, Baram-Tsabari, & Lewestein, 2011, p. 865).…”
Section: Understanding Reactions To Celebrity Narratives Through Onlimentioning
confidence: 99%
“…This research demonstrated effects of online social proof in a large variety of contexts, such as organic food (Hilverda, Kuttschreuter, & Giebels, ), breastfeeding attitudes (Jin, Phua, & Lee, ), marihuana legalization (Winter, Bruckner, & Kramer, ), brand engagement and sales (Kim & Johnson, ), and vaccination (Peter, Rossmann, & Keyling, ). There is also empirical evidence with respect to other social media, such as YouTube (Shi, Messaris, & Cappella, ; Walther, DeAndrea, Kim, & Anthony, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the empirical evidence for the effect of (online) social proof is not restricted to Facebook. Studies have also shown the effect of social proof on YouTube, for example in relation to smoking behavior (Walther et al, 2010;Shi et al, 2014).…”
Section: Theory Online Social Proof: Comments Narratives and Other mentioning
confidence: 99%
“…While previous research on online social proof mainly focused on topics on which consumers generally hold negative attitudes, such as smoking (Walther et al, 2010;Shi et al, 2014), our research focused on a topic that is generally viewed as positive, namely organic food products. Food is something that is relevant to all of us, as we all have to eat.…”
Section: Introductionmentioning
confidence: 99%